The reliability and criterion validity of 2D video assessment of single leg squat and hop landing - Herrington, L.; Alenezi, F.; Alzhrani, M.; Alrayani, H.; Jones, R. (Journal of Electromyography and Kinesiology, 2017)
The objective was to assess the intra-tester, within and between day reliability of measurement of hip adduction (HADD) and frontal plane projection angles (FPPA) during single leg squat (SLS) and single leg landing (SLL) using 2D video and the validity of these measurements against those found during 3D motion capture. 15 healthy subjects had their SLS and SLL assessed using 3D motion capture and video analysis. Inter-tester reliability for both SLS and SLL when measuring FPPA and HADD show excellent correlations (ICC2,1 0.97-0.99). Within and between day assessment of SLS and SLL showed good to excellent correlations for both variables (ICC3,1 0.72-91). 2D FPPA measures were found to have good correlation with knee abduction angle in 3-D (r = 0.79, p = 0.008) during SLS, and also to knee abduction moment (r = 0.65, p = 0.009). 2D HADD showed very good correlation with 3D HADD during SLS (r = 0.81, p = 0.001), and a good correlation during SLL (r = 0.62, p = 0.013). All other associations were weak (r < 0.4). This study suggests that 2D video kinematics have a reasonable association to what is being measured with 3D motion capture.